2019
DOI: 10.3389/fpsyg.2019.01144
|View full text |Cite
|
Sign up to set email alerts
|

Does the Disease of the Person Receiving Care Affect the Emotional State of Non-professional Caregivers?

Abstract: Research on mental health of non-professional caregivers has focused on caregivers of people with specific diseases, especially dementia. Less is known about caregivers of people with other diseases. The aims of this study were (a) to determine the caregivers’ emotional state in a random sample of caregivers of people in situations of dependency, (b) to analyze the association between each disease of the care-recipient (a variety of 23 diseases included in the International Classification of Diseases) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
2
4
0
1
Order By: Relevance
“…As estimated, 75% of the patients with dementia are cared for by family caregivers (Li et al, 2019; Stensletten et al, 2014), such as family members, relatives and friends (Wawrziczny et al, 2017). Lin et al (2019) found that caregivers had increased burden to take care of activities of daily living and neuropsychiatric symptoms of people with dementia and caregivers also suffered from moderate emotional distress (Caceres et al, 2016; Otero et al, 2019), depression and anxiety (Qiu et al, 2019), grief (Li et al, 2019; Sanders et al, 2007), stress (Correa et al, 2019; Podgorski, 2018), burden (Allen et al, 2017; Yu et al, 2018) and affiliate stigma (Chang et al, 2016; Saffari et al, 2019; Su & Chang, 2020). These negative emotional reactions ultimately result in negative effects on family caregivers' health, both physically and mentally (Meichsner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As estimated, 75% of the patients with dementia are cared for by family caregivers (Li et al, 2019; Stensletten et al, 2014), such as family members, relatives and friends (Wawrziczny et al, 2017). Lin et al (2019) found that caregivers had increased burden to take care of activities of daily living and neuropsychiatric symptoms of people with dementia and caregivers also suffered from moderate emotional distress (Caceres et al, 2016; Otero et al, 2019), depression and anxiety (Qiu et al, 2019), grief (Li et al, 2019; Sanders et al, 2007), stress (Correa et al, 2019; Podgorski, 2018), burden (Allen et al, 2017; Yu et al, 2018) and affiliate stigma (Chang et al, 2016; Saffari et al, 2019; Su & Chang, 2020). These negative emotional reactions ultimately result in negative effects on family caregivers' health, both physically and mentally (Meichsner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…23 The caregiver stress process generated by the care situation, socio-demographic characteristics (i.e., as age, gender, educational level, marital status, and social class of the caregiver, relationship with and gender of the patient) are related to primary stressors (i.e., the patient's disease, dependence level of the patient, duration and daily hours of care), and that primary and secondary stressors (i.e., employment, monthly family income and caregivers' self-esteem) are related to caregivers' emotional state. 24 The job of caregiving is burdensome and it definitely affects the physical and psychological health of caregivers negatively.…”
Section: Whether Caregiving Causes Burden or Distress?mentioning
confidence: 99%
“…Otero és mtsai kutatási [28] eredményei megerősítik, hogy a hasonló gondozási helyzet is különböző megterheltségérzettel járhat, hiszen a megterheltséget jelentősen befolyásolják az erőforrások és a megküzdési módok. Kiemelik, hogy a társas támogatás védőfaktort jelenthet a gondozás objektív terheit és a gondozással járó érzelmi disstresszek következményeit illetően is.…”
Section: Megbeszélésunclassified